Egalitarian Essentialism: Why Egalitarian Women Opt for Binding Moral Foundations within the Family Structure - Iwan Zaenul Fuad; Ahmad Fauzan; Abdul Hamid; Anindya Aryu Inayati; Siti Mumun Muniroh (PT PUSTAKA CENDEKIA GROUP, 2026)
This study explores the moral foundations upheld by Indonesian women within their household context, utilizing the Conjugal Moral Foundations Questionnaire (CMFQ)—a modified version of the Moral Foundations Questionnaire (MFQ) specifically tailored for the marital setting. The study reveals that Indonesian women generally prioritize traditional moral values, showing the highest preference for the foundations of care, loyalty, and sanctity. However, we identify a significant Moral Dissonance—a measurable gap between moral expectations and moral actions—particularly pronounced across the care, fairness, and authority foundations. This study argues that this dissonance is resolved through a cognitive mechanism termed Egalitarian Essentialism. This mechanism manifests in women’s moral preference for distributive justice (a balance between rights/obligations and responsibilities) over commutative justice (pure equality), alongside their conditional recognition of male dominance (patriarchy) in household leadership. These findings offer critical insights into the moral complexity of women in the Indonesian household, serving as a vital basis for developing targeted programs and policies that support family well-being. Further research is necessary to track the temporal dynamics of marital moral relations and to explore justice preferences within the household more deeply.